Research of collision probability behaviour the appreciated behind a method of the rare events modelling at optimum sample - Бабак, В.П.; Харченко, В.П.; Знаковська, Є.А. (Proceedings of National Aviation University (archive), 2004)
The collision probability behaviour the researched behind a method of the rare events modelling at optimum subsidiary sample by change of distribution parameters is resulted.